2011
DOI: 10.1111/j.2044-8317.2011.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ignoring multiple membership data structures in multilevel models

Abstract: This study compared the use of the conventional multilevel model (MM) with that of the multiple membership multilevel model (MMMM) for handling multiple membership data structures. Multiple membership data structures are commonly encountered in longitudinal educational data sets in which, for example, mobile students are members of more than one higher-level unit (e.g., school). While the conventional MM requires the user either to delete mobile students' data or to ignore prior schools attended, MMMM permits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 25 publications
15
104
0
Order By: Relevance
“…In addition, rates similar to these have been used in other educational mobility simulation studies (Chung & Beretvas, 2012;Grady, 2010;Luo & Kwok, 2012). Last, the low mobility rate value is similar to the mobility rate found in the real data analysis (11.4%).…”
Section: Mobility Ratesupporting
confidence: 58%
See 3 more Smart Citations
“…In addition, rates similar to these have been used in other educational mobility simulation studies (Chung & Beretvas, 2012;Grady, 2010;Luo & Kwok, 2012). Last, the low mobility rate value is similar to the mobility rate found in the real data analysis (11.4%).…”
Section: Mobility Ratesupporting
confidence: 58%
“…Differences between multiple membership and typical multilevel models that ignore the multiple membership structure for baseline unconditional fixed effects estimates have not frequently been found in previous research (Chung & Beretvas, 2012;Grady, 2010;Luo & Kwok, 2009;Luo & Kwok, 2012;Meyers & Beretvas, 2006). However, in a study by Smith (2012), substantial positive relative parameter bias was found when estimating the level-1 predictor for the MMREM and HLM models, which was attributed to model misspecification.…”
Section: Baseline Unconditional Fixed Effectsmentioning
confidence: 82%
See 2 more Smart Citations
“…As for now, optimal design recommendations for such trials are lacking. Another example is multiple membership models, see Chung and Beretvas (2012), Luo and Kwok (2012) for the implications of ignoring multiple membership structures, and Roberts and Walwyn (2013) for optimal design methodology. Thus far, the main focus has been on linear models with continuous outcome scores; future research should focus on dichotomous outcome scores.…”
Section: Conclusion and Discussionmentioning
confidence: 99%